2018
DOI: 10.1093/bioinformatics/bty810
|View full text |Cite
|
Sign up to set email alerts
|

A clustering linear combination approach to jointly analyze multiple phenotypes for GWAS

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(84 citation statements)
references
References 58 publications
(40 reference statements)
1
83
0
Order By: Relevance
“…One of the clusters contains phenotypes FEV1, Emph, and GasTrap, while the other four clusters each contain only a single phenotype. All of these 14 SNPs were previously reported to be associated with COPD (Brehm et al, 2011;Cho et al, 2010;Cho et al, 2014;Cui, Ge, & Ma, 2014;Du, Xue, & Xiao, 2016;Hancock et al, 2010;Li et al, 2011;Liang, et al, 2018;Lutz et al, 2015;Pillai et al, 2009;Sha et al, 2018;Wilk et al, 2009;Wilk et al, 2012;Young et al, 2010;Zhang, Summah, Zhu, & Qu, 2011;Zhu et al, 2014). Table 2 summarizes the 14 significant SNPs that have been identified by at least one of the six methods.…”
Section: Real Data Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the clusters contains phenotypes FEV1, Emph, and GasTrap, while the other four clusters each contain only a single phenotype. All of these 14 SNPs were previously reported to be associated with COPD (Brehm et al, 2011;Cho et al, 2010;Cho et al, 2014;Cui, Ge, & Ma, 2014;Du, Xue, & Xiao, 2016;Hancock et al, 2010;Li et al, 2011;Liang, et al, 2018;Lutz et al, 2015;Pillai et al, 2009;Sha et al, 2018;Wilk et al, 2009;Wilk et al, 2012;Young et al, 2010;Zhang, Summah, Zhu, & Qu, 2011;Zhu et al, 2014). Table 2 summarizes the 14 significant SNPs that have been identified by at least one of the six methods.…”
Section: Real Data Analysis Resultsmentioning
confidence: 99%
“…if the k th phenotype belongs to the l th cluster or otherwise b = 0 kl , and Σ is the variance-covariance matrix of T. Sha et al (2018) showed that Σ can be estimated by the sample correlation matrix of the K phenotypes. Under the null hypothesis that none of phenotypes are associated with the genetic variant, T CLC L follows a χ 2 distribution with degrees of freedom equal to L. Since for a given data set, the number of clusters of the phenotypes is unknown, in the last step of the CLC method, we use…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides detecting colocalization of possibly causal SNPs for a GWAS trait and a molecular trait like gene expression, it is also of interest for colocalization analysis of multiple complex traits or diseases, which for example may be helpful for understanding the shared biological pathways for multiple diseases and thus for drug repurposing and new therapeutic development. Studies have found that some diseases seem to have commonly associated genetic variants [14,15], which by themselves cannot determine colocalization either; when a variant is associated with multiple traits, it could be due to distinct causal SNPs that are in linkage disequilibrium (LD) [16], which however can be distinguished through joint/conditional modeling of multiple SNPs as in fine mapping [17,18,19]. This critical difference between marginal and conditional associations also highlights the difference between the existing pleiotropy testing [20,21] and the proposed colocalization testing on multiple traits.…”
Section: Introductionmentioning
confidence: 99%
“…Existing methods for joint analysis on genetic data are mostly built on summary statistics (e.g., McGeachie et al, 2014;Giambartolomei et al, 2014;Kang et al, 2014;Zhu et al, 2015;Bulik-Sullivan et al, 2015;Nieuwboer et al, 2016;Hu et al, 2017;Wen et al, 2017;Liu et al, 2017;Sha et al, 2018;Guo and Wu, 2018) More recently, Turley et al (2018) introduced multi-trait analysis of GWAS (MTAG) that can perform joint analysis using the summary statistics calculated from cohorts with overlapping samples. Zeng et al (2018) proposed a regularized Gaussian mixture model called iMAP to infer the association between SNPs to correlated phenotypes.…”
Section: Introductionmentioning
confidence: 99%